The relationship between negative trauma-related cognitions and psychosocial functioning in veterans with posttraumatic stress disorder and alcohol use disorder. Issue 1 (2nd January 2020) - Lyons, Robert; Haller, Moira; Curry, Inga; Norman, Sonya B.
Abstract: Background: The comorbidity of posttraumatic stress disorder (PTSD) and alcohol use disorder (AUD) is highly prevalent and associated with especially poor psychosocial functioning. Negative trauma-related cognitions are theoretically proposed to be associated with poor psychosocial functioning in PTSD, but few studies have examined the association between negative trauma-related cognitions and psychosocial functioning in PTSD/AUD. Evaluating this association may provide evidence of a potential treatment target for improving psychosocial functioning in PTSD/AUD. We hypothesized that negative trauma-related cognitions, including cognitions about the self, world, and self-blame, would be independently associated with poor psychosocial functioning in the following domains: vitality, psychosocial well-being, role limitations due to emotional distress, and social functioning. Methods: We examined the relationship between negative trauma-related cognitions and psychosocial functioning in 145 treatment-seeking veterans with PTSD/AUD using multiple linear regression analyses while controlling for PTSD and alcohol abuse and dependence severity. Results: Our hypotheses were partially supported. We found that negative trauma-related cognitions were uniquely associated with greater psychosocial functional impairment, independent of PTSD and alcohol abuse and dependence severity. Specifically, negative trauma-related cognitions about the self were associated with greater psychosocial functional impairment across all domains, cognitions about the world were associated with worse social functioning and psychological well-being, and self-blame was associated with impaired psychological well-being. Conclusions: Given that improvements in negative trauma-related cognitions are a mechanism of trauma-focused treatment, future studies should examine whether changes in negative trauma-related cognitions through trauma-focused treatment are associated with improved psychosocial functioning.